A historic overview of oriental solmisation systems followed by an inquiry into the current use of solmisation in aural training at South African universities - Louw, Theunis Gabriël (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMus (Music)) -- Stellenbosch University, 2010.